2008
DOI: 10.1634/theoncologist.2007-0191
|View full text |Cite
|
Sign up to set email alerts
|

Managing Vesicant Extravasations

Abstract: After completing this course, the reader will be able to:1. Describe how vesicant chemotherapy drugs can extravasate from implanted ports.2. Recommend procedures to obtain a blood return from central venous access devices.3. Evaluate the signs and symptoms of a vesicant extravasation. Administer the FDA-approved vesicant extravasation treatments and antidotes.Access and take the CME test online and receive 1 AMA PRA Category 1 Credit ™ at CME.TheOncologist.com CME CME ABSTRACTExtravasation is an unusual but po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 10 publications
0
26
1
1
Order By: Relevance
“…Preventive measures are strongly advocated in the the nurse (4,(7)(8) . However, in this study it was not possible to identify preventive measures established by the nursing team in their records, except for the complaints of women during infusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventive measures are strongly advocated in the the nurse (4,(7)(8) . However, in this study it was not possible to identify preventive measures established by the nursing team in their records, except for the complaints of women during infusion.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no consensus about localized drug use, the local application of ice for all drugs, except for the vinca alkaloids and oxaliplatin, when heat should be used, is an empirical measure used for many years, but with no evidence of benefits (7)(8)(9) . The protocol used in the service where this study was conducted is consistent with that suggested in the international literature, except for the use of sodium bicarbonate, which has not been recommended for its vesicant effect when given outside the vessel (8)(9) .…”
Section: Resultsmentioning
confidence: 99%
“…Hastaya kemoterapi tedavisine başlanma-dan önce kemoterapinin yan etkileri, komplikasyonları, riskleri, yararları, fizyolojik ve psikolojik etkileri hakkında bilgilendirme yapılmalıdır (10,19 …”
Section: Hasta Eğitimiunclassified
“…Mrs. Zatkó reported complications with "no serious consequences" (but not precisely determined) in case of 0.1 %, but the incidence of all events is not detailed 2 . The risk of extravasation can be reduced significantly by using centrally vein accessed ports and subcutaneously implanted "reservoirs" (subcutaneously implanted ports), but using this method cannot even guarantee to avoid this complication and in addition to the effects of cytostatic agents escaping into the tissues centrally, also unusual complications may develop [5,10,11,[18][19][20][21][22][23][24][25][26][27] .…”
Section: Incidence Of Extravasation and The Possibility Of Risk Incrementioning
confidence: 99%